Exploring the potentials of lean-burn hydrogen SI engine compared to methane operation. (12th July 2022) - Sementa, Paolo; de Vargas Antolini, Jácson Beltrão; Tornatore, Cinzia; Catapano, Francesco; Vaglieco, Bianca Maria; López Sánchez, José Javier
Abstract: The global rush for decarbonization and the more restrictive emission regulations are pushing the research for cleaner powertrains to the transport sector. In this sense, this work contributes with an experimental investigation of the performance and emissions of a single-cylinder SI engine operating under lean-burn hydrogen combustion. Its performance, combustion parameters, exhaust emissions, and indicated efficiency for a wide range of mixture dilutions are then compared to methane under similar engine load conditions. Hydrogen achieved stable combustion up to lambda 3.4, presenting zero CO emission and very low HC emission for all tested operating conditions. Hydrogen operation also presented zero NOx emissions for conditions leaner than lambda 2.2 and 3.0 at 2000 and 3000 rpm, respectively, however, the NOx emissions increase as the mixture is enriched. The high in-cylinder pressure rise rate limited the operation at mixtures richer than lambda 1.3 at 2000 rpm. When compared to methane, the hydrogen allows de-throttle the engine to burn lean mixtures maintaining a proper flame speed, resulting in lower pumping losses, lower pollutants emissions for most of the conditions tested, and higher indicated efficiency, making hydrogen a promising fuel to replace conventional fuels on cleaner SI engines. Highlights: H2 de-throttled operation decreased pumping losses and increased indicated efficiency. H2 presented higher indicated efficiency than CH4 for all operating condition. H2 presented zero NOx emissions at λ = 2.2 and 3.0 at 2000 and 3000 rpm, respectively. H2 direct-injection ensured knock-safe operation for all tested conditions. Very lean H2 mixtures require alternative strategies to shorten combustion duration.